A model for enhancing value addition in chili farming to support food security and SDGs in Indonesia - Fafurida; Sakitri, Wijang; Adzim, Fauzul; Nihayah, Annis Nurfitriana; Pertiwi, Meilani Intan (Journal of Food Technology Research, 2025)
This study aims to develop a model that enhances the value of chili farming, with the objectives of improving food security and contributing to the achievement of the Sustainable Development Goals (SDGs) in Central Java. The research employs a mixed-method approach, integrating quantitative data from surveys and Hayami value-added analysis with qualitative insights from interviews, observations, and group discussions. Data analysis involves Hayami analysis to quantify value addition during chili processing into powder, interregional input-output (IRIO) analysis to assess the economic impact of chili farming on related sectors, and Importance Performance Analysis (IPA) to identify strategic priorities for value enhancement. The findings indicate that processing chili into powder increases its value by 34%, with a profit margin of 25%, thereby increasing farmers’ income and generating employment opportunities. The IRIO analysis reveals that the chili processing industry in Central Java is highly interconnected with other industries, particularly in DKI Jakarta and East Java. The IPA results suggest that improving access to high-quality raw materials, facilitating easier loan access, providing better training for workers, and developing effective marketing strategies are essential for sector development. The study confirms that an integrated approach, emphasizing cross-sector collaboration, institutional strengthening, production efficiency, and market-oriented processing, is necessary to build an effective model for increasing chili’s added value. The implications of this model extend beyond competitiveness, supporting poverty alleviation, food security, and sustainable industrialization aligned with the SDGs framework.